Cak Nur dan Liberalisasi Islam:Nalar Pembaruan Pemikiran Islam Nurcholish Madjid - Muhammad Sahlan; Dendy Wahyu Anugrah (4, 2026)
So far, the idea of reforming Islamic thought put forward by Nurcholish Madjid is still being studied as an intellectual movement that has a significant influence on the development of Islamic thought in Indonesia. So that the concept of thought renewal initiated by Nurcholish Madjid (Cak Nur) tends to be only described descriptively, without further reviewing how the reason used in demonstrating the renewal of Islamic thought. Therefore, this article wants to analyze the reasoning position of Cak Nur's Islamic thought reform which is sourced from the paper